Reconstructing discards profiles of unreported catches - Leitão, Francisco (2019)
In Portugal it has been estimated that unreported catches represent one third of total catches. Herein, information on landings and total unreported catches (discards) by commercial métier were disaggregated into high taxonomic detail using published scientific studies. Fish accounted for 93.5% (115493 t) of overall unreported catches per year, followed by cephalopods (2345 t, 1.9%) and crustaceans (1754 t, 1.4%). Sharks accounted for 1.3% of total unreported catches in weight (1638 t/y). Unreported taxa consisted mostly of the commercial landed fish species: Scomber colias, Boops boops, Trachurus picturatus, T. trachurus, Merluccius merluccius, Sardina pilchardus, Liza aurata and Micromesistius poutassou, which together accounted for 70% of the unreported discarded catches. The number of unreported/discarded species was highest in artisanal fisheries, followed by trawl and purse seine. In artisanal fisheries, L. aurata, S. colias, S. pilchardus, Trachinus draco and B. boops accounted for 76.4% of the unreported discards. B. boops, S. colias and S. pilchardus were also among the most discarded purse seine species, together with Belone belone accounting for 79% of the unreported catches. In trawl fisheries, T. picturatus (16%), M. merluccius (13%), S. colias (13%) and M. poutassou (13%) accounted for 55% of the trawl discarded unreported catches. The discarded species that most contribute to overall unreported catches are those that are most frequently landed and that most contribute to overall landings in weight.